Effect of Mg xZn 1-xO thin film as barrier layer for efficiency improvement of ZnO dye-sensitized solar cells - Atip Pengpad (2018)
M Mg xZn 1-xO (MZO) thin films were used as a barrier layer for efficiency improvement of ZnO dye-sensitized solar cells (DSSCs) by controlling charge recombination dynamics. The effect of barrier layer was investigated in terms of the thickness of MZO layer by varying sputtering time. The MZO films were characterized by scanning electron microscopy, energy dispersive X-ray spectroscopy and UV-visible spectroscopy. The DSSCs were investigated by using J-V measurement and electrochemical impedance spectroscopy. It was found that DSSCs with 1 minute MZO sputtering time exhibited the highest power conversion efficiency of 0.82% which was higher than that of DSSC without MZO film. This could be explained in terms of suppression of back electron transfer in recombination process. However, DSSCs with longer sputtering time exhibited lower current density and efficiency. The lower current density was caused by lower electron injection due to higher resistance of MZO. Thus, MZO layer can be used as a barrier layer to control charge-transfer process and can improve the efficiency of ZnO DSSCs.